Analisis Kebijakan dan Problematika Sertifikasi Guru Jalur Portopolio dalam Kebijakan Pendidikan Nasional - Ramlan, Ramlan; Isroani, Farida (Faidatuna, 2020)
Educational activity is a process that is designed in such a way and applied formally and measurably with the hope of achieving maximum and effective goals, especially the goals of national education as stated in article 3 of Law no. 20 of 2003. In achieving this National education goal, this goal was designed by experts in the national capital while the humans who serve as this national goal are in areas with different cultures and intelligences, as well as teachers who carry out the heavy task must be able to describe and interpret Law no. 20 of 2003 must be able to achieve this at the same time, besides the teacher's responsibility to educate the nation's children, teachers also have responsibilities that are no less serious towards their families, both economic and other responsibilities. It is very wise for the government to pay more attention to teachers with a policy of providing additional financial income from the professionalism of teachers, namely a professional allowance of 100% of the basic salary, teacher professionalism is a condition for obtaining this allowance and to be recognized as a professional teacher, teachers must meet various requirements. as evidenced by the portfolio collected. Unfortunately in the collection of fortopolio there are many loopholes for dishonesty by some unscrupulous teachers where the skills and professionalism of the teacher are not as what the fortopolio explains, because fortopolio can be obtained without strict selection, so teachers who are considered professional by the state and have been given the trust to educating the nation's children and have been rewarded with a professional allowance (which is called a certification allowance) even though not all certified teachers are necessarily professional, because fortopolio is easy to manipulate.